The Role Of Fractions In The Formation Of Regional Regulation Number 4 oF 2020 Concerning the Election of Village Heads in Limboto District - Karunggu, Salitan; Sakir , Mochammad; Swastiani Dunggio, Swastiani Dunggio; Gaffar, Gaffar (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2025)
The aim of this research is to find out the role of factions in the formation of Regional Regulation Number 4 of 2020 concerning the Election of Village Heads in Limboto Regency. This research uses a qualitative approach with descriptive methods. Data collection techniques in this research used interviews, observation and documentation, with data analysis techniques using interactive models. The results of the study indicate that the role of the faction in the formation of Regional Regulation Number 4 of 2020 concerning Village Head Elections in Limboto Regency began when the faction collected community aspirations, which were then brought to the faction meeting to be used as input for revising the previous regulation. Because Regional Regulation Number 4 of 2020 was an initiative proposal from the Gorontalo Regency Regional People's Representative Council, the proposed draft regional regulation was submitted to the DPRD leadership and then brought to the DPRD Plenary Session for discussion. In this plenary session, the faction also played a role in conveying community aspirations by providing proposals, input, or criticism and even providing suggestions. The results also showed that some community members sometimes expressed their aspirations for the organization or reminded the DPRD about problems within the faction, but sometimes several DPRD members were often absent from the faction meeting room. In addition, due to the inadequate education and socialization efforts carried out by the Gorontalo Regency DPRD in the Fraction, most of the community also did not know the goals, duties, or other functions of the organization. Tujuan penelitian ini adalah untuk mengetahui bagaimana peran fraksi partai politik di DPRD dalam pembentukan Peraturan Daerah Nomor 4 Tahun 2020 Tentang Pemilihan Kepala Desa di Kabupaten Limboto. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dalam penelitian ini menggunakan wawancara, observasi dan dokumentasi, dengan teknik analisis data menggunakan model interaktif. Hasil penelitian menunjukkan bahwa peran fraksi dalam pembentukan Peraturan Daerah Nomor 4 Tahun 2020 Tentang Pemilihan Kepala Desa di Kabupaten Limboto, sudah dimulai pada saat penjaringan aspirasi masyarakat oleh fraksi, yang kemudian dibawa ke rapat fraksi yang akan dijadikan bahan masukan untuk revisi perda sebelumnya. Karena Peraturan Daerah Nomor 4 Tahun 2020 merupakan usulan inisiatif Dewan Perwakilan Rakyat Daerah Kabupaten Gorontalo, maka usulan rancangan peraturan daerah itu disampaikan kepada pimpinan DPRD kemudian dibawa ke Sidang Paripurna DPRD untuk dibahas. Dalam sidang paripurna ini, fraksi juga memainkan peranannya membawa aspirasi masyarakat dengan memberikan usulan, masukan, atau kritik dan bahkan memberikan saran. Hasil penelitian juga menunjukkan bahwa beberapa anggota masyarakat kadang-kadang mengungkapkan aspirasi mereka untuk organisasi atau mengingatkan DPRD tentang masalah di dalam fraksi, namun terkadang beberapa anggota DPRD sering absen. dari ruang rapat fraksi. Di samping itu, akibat kurang memadainya upaya pendidikan dan sosialisasi yang dilakukan DPRD Kabupaten Gorontalo di Fraksi, sebagian besar masyarakat juga tidak mengetahui tujuan, tugas, atau fungsi lain dari organisasi tersebut Kata kunci: peran fraksi; Pemilihan Kepala Desa